Negotiating Work/Life Balance : the Experience of Fathers and Mothers in Ireland - DREW, EILEEN PATRICIA (UCL (Belgium), 2007)
Working arrangements are still not sufficiently flexible to enable parents to manage to fulfil their roles as workers and as carers and there remains a dearth of flexible working arrangements and work-life balance policies especially for fathers. This paper examines the degree of work/life balance among fathers, and mothers, employed in 5 major Irish organisations surveyed in 2002. It concentrates on the access to, and take up of, flexible working time and leave arrangements by fathers and mothers and explores the impact of such arrangements on their careers and their attitudes towards work/life balance. Parents were asked about their actual and preferred childcare arrangements. The majority of fathers were able to rely upon the provision of care by the mother in their own home - an option that was available to only a small proportion of mothers. The paper concludes by discussing the kinds of work/life balance interventions/measures sought by fathers and mothers.
PUBLISHED
Keywords: Gender; Work / life balance; Working mothers; Working fathers